Politik Hukum Islam dalam Regulasi Wakaf - Dedi Anton Ritonga; Putra Halomoan Hasibuan (Lembaga Pengembangan Kinerja Dosen, 2025)
Human Rights This paper discusses the study of Islamic legal politics and the substance of changes in waqf regulation in Indonesia, particularly in Government Regulation (PP) Number 25 of 2018, which amends Government Regulation Number 42 of 2006. This study seeks to analyze how the approach of Islamic legal politics is applied in responding to the evolving needs of waqf management, in line with the times and the demands of national development, while still aligning with the fundamental principles of Islamic law (sharia). The amendment in Government Regulation No. 25 of 2018 specifically clarifies the mechanism of waqf asset exchange (ruislag) by prioritizing the principles of public benefit (maslahah), accountability, and protection of the waqif’s intent. A normative-juridical approach is employed to analyze this regulation within the framework of maqashid al-sharia and the context of national legal policy. The results of this study indicate that the changes in Government Regulation No. 25 of 2018 have a significant impact on the governance of waqf, making it more transparent and accountable. This impact is the result of the presence of Islamic legal politics in integrating sharia principles with the practical needs of waqf governance. It also encourages waqf policymakers in Indonesia to optimize the potential of waqf in building a just society through sharia-based financial institutions that serve the broader Muslim community.